On an Intervention Regarding Dialectics in Marx and Hegel by Marcos LutzMüller (1982) (Revista Eletrônica Estudos Hegelianos, 2024)
Marcos Lutz Müller, widely known for his translations and commentaries on Hegel, also contributed to a certain renewal of Marx studies in Brazil. This article aims to reconstruct elements of the historical scenario in which his 1982 intervention in the debates on Marx’s dialectics occurred.